Epigenetic control of tissue resident memory T cells - Lan, Zhiyi; Chen, Zeyu; Yang, Nan; Liu, Tong; Li, Siqi; Shi, Yuling; Gu, Jun (Frontiers in Immunology, 2025)
Tissue-resident memory T cells (TRM) represent a heterogeneous population of T cells that exhibit both effector and memory functionalities. They express specific gene signatures that enable them to occupy tissues without recirculating, thus providing a first response against reencountered pathogens or antigens. TRM have been implicated in the pathogenesis of various diseases, including autoimmune disorders, infections, and cancers. This has prompted interest in targeting TRM as a potential therapeutic strategy. Epigenetic modifications, which frequently occur in immune cells across various disease states, play a significant role not only in tissue homeostasis but also in disease progression. Emerging evidence suggests that the epigenetic landscape of TRM is altered in pathogenic conditions, impacting their differentiation, maintenance, and function. Nevertheless, the precise mechanisms remain poorly understood. This review seeks to provide a comprehensive overview of the epigenetic regulation of TRM, focusing on key areas such as chromatin accessibility, DNA methylation, histone modifications, and non-coding RNAs. Importantly, a deeper understanding of these epigenetic mechanisms will pave the way for novel therapeutic strategies, such as modulating TRM activity in autoimmune diseases, enhancing tissue-specific immunity through vaccines, or improving immunotherapeutic efficacy in cancer.